Expression of Na+/H+ exchanger regulatory factor 1 in autosomal-dominant polycystic kidney disease. (October 2015) - Wang, Jian-Qing; Qin, Fu; Zhu, Liang
Objective: To explore the role of Na + /H + exchanger regulatory factor 1 (NHERF1) in autosomal-dominant polycystic kidney disease (ADPKD). Methods: NHERF1 and β-catenin protein were detected by immunohistochemistry and Western blotting of kidney tissue samples from patients with ADPKD and controls (normal kidney tissue [>5 cm from the foci] collected from patients undergoing unilateral nephrectomy for kidney cancer). NHERF1 and β-catenin protein and mRNA were quantified by Western blot and real-time fluorescent quantitative polymerase chain reaction, respectively, in kidney tissue samples from Han:SPRD (+/+) and (cy/+) rats. The effects of human recombinant NHERF1 on proliferation and cell cycle of ADPKD cyst-lining epithelial cells (WT9–12) were evaluated by MTT assay and flow cytometry, respectively. Results: Levels of NHERF1 protein and mRNA were significantly lower, and β-catenin levels significantly higher, in patients with ADPKD and Han:SPRD (cy/+) rats, compared with control subjects and (+/+) rats, respectively. Exogenous recombinant NHERF1 significantly inhibited proliferation of WT9–12 cells and increased the proportion of cells in G0 /G1 phase. Conclusions: ADPKD is associated with a decrease in NHERF1 protein and mRNA levels. Supplementing exogenous NHERF1 inhibited the proliferation of WT9–12 cells.